The Influence of Teachers’ Performance, Emotions, Attitude and Beliefs on Educational Reforms in Tulungagung, Indonesia: Mediating Role of Supply Chain - Maunah, Binti (International Journal of Supply Chain Management, 2020)
Abstract- The aim of the current study is to inspect the influence of teachers’ performance, emotions, attitudes and beliefs on the educational reforms in the Tulungagung, Indonesia. While another aim of the existing research is to analyze the mediating effects of the supply chain on the links among the teachers’ performance and educational reforms, teachers’ emotions and educational reforms, teachers’ attitudes and educational reforms and teachers’ beliefs and educational reforms. The data was collected from the government higher secondary educational institutionsthat are working under the territory of Tulungagung, Indonesia. For the analysis purposes, PLS-SEM was used in this study. The findings uncovered that positive nexus among the teachers’ performance, emotions, attitudes, beliefs and educational reforms. The outcomes also uncovered that the supply chain significantly as well as positively influenced the links among the teachers’ performance and educational reforms, teachers’ emotion and educational reforms, teachers’ attitudes and educational reforms and teachers’ beliefs and educational reforms. This research provides the guidelines to the regulations making authorities that they should develop and implement the regulations that enhance the above-mentioned characteristics of the teachers that enhance the educational reforms within the educational institution in Indonesia.